2019
DOI: 10.21873/cgp.20152
|View full text |Cite
|
Sign up to set email alerts
|

The FOXC2 Transcription Factor Promotes Melanoma Outgrowth and Regulates Expression of Genes Associated With Drug Resistance and Interferon Responsiveness

Abstract: Background/Aim: The FOXC2 transcription factor promotes the progression of several cancer types, but has not been investigated in the context of melanoma cells. To study FOXC2's influence on melanoma progression, we generated a FOXC2-deficient murine melanoma cell line and evaluated The Cancer Genome Atlas (TCGA) patient datasets. Materials and Methods: We compared tumor growth kinetics and RNA-seq/qRT-PCR gene expression profiles from wild-type versus FOXC2-deficient murine melanomas. We also performed Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Our recent study highlighted several differentially expressed genes upregulated in B16-F1 that are associated with GO Terms related to the cellular response to xenobiotics and oxidative stress. We also noted in that study the downregulation in B16-F1 of several genes associated with GO Terms related to IFN responsiveness (16). Our current KEGG Pathway analysis supports these findings, with significant enrichment of B16-F1 upregulated genes in pathways related to xenobiotic metabolism and glutathione metabolism as well as significant enrichment of B16-F1 downregulated genes in pathways related to viruses and Nod-like receptor signaling, all of which include several genes involved in cellular responses to IFN.…”
Section: Overview and Reuse Of Datasupporting
confidence: 84%
See 4 more Smart Citations
“…Our recent study highlighted several differentially expressed genes upregulated in B16-F1 that are associated with GO Terms related to the cellular response to xenobiotics and oxidative stress. We also noted in that study the downregulation in B16-F1 of several genes associated with GO Terms related to IFN responsiveness (16). Our current KEGG Pathway analysis supports these findings, with significant enrichment of B16-F1 upregulated genes in pathways related to xenobiotic metabolism and glutathione metabolism as well as significant enrichment of B16-F1 downregulated genes in pathways related to viruses and Nod-like receptor signaling, all of which include several genes involved in cellular responses to IFN.…”
Section: Overview and Reuse Of Datasupporting
confidence: 84%
“…Another previously unappreciated function of FOXC2 revealed by our data is its negative regulation of genes associated with IFN signaling, a finding that is particularly intriguing in light of recent studies demonstrating that both type I IFN and IFNγ signaling pathways within tumor cells are critical to the efficacy of cancer immunotherapies (34)(35)(36)(37). Indeed, our recent analysis of melanoma patient TCGA data showed that FOXC2 expression correlates negatively with progression-free survival (PFS) of patients treated with the CTLA-4 immune checkpoint inhibitor ipilimumab (16). Though the mechanism by which FOXC2 might promote resistance to checkpoint blockade therapy remains to be elucidated, it is interesting that in our murine model FOXC2 negatively regulated the expression of several IFN signaling pathway components, including the Ddx58 gene encoding RIG-I and the Stat1/Stat2/Stat3 and Irf7/Irf9 transcription factor genes.…”
Section: Overview and Reuse Of Datamentioning
confidence: 53%
See 3 more Smart Citations